Studies on Fragment-Based Design of Allosteric Inhibitors of Human Factor XIa - Boothello, Rio S. (Bioorg Med Chem, 2020)
Human factor XIa (hFXIa) has emerged as an attractive target for development of new anticoagulants that promise higher level of safety. Different strategies have been adopted so far for the design of anti-hFXIa molecules including competitive and non-competitive inhibition. Of these, allosteric dysfunction of hFXIa’s active site is especially promising because of the possibility of controlled reduction in activity that may offer a route to safer anticoagulants. In this work, we assess fragment-based design approach to realize a group of novel allosteric hFXIa inhibitors. Starting with our earlier discovery that sulfated quinazolinone (QAO) bind in the heparin-binding site of hFXIa, we developed a group of two dozen dimeric sulfated QAOs with intervening linkers that displayed a progressive variation in inhibition potency. In direct opposition to the traditional wisdom, increasing linker flexibility led to higher potency, which could be explained by computational studies. Sulfated QAO 19S was identified as the most potent and selective inhibitor of hFXIa. Enzyme inhibition studies revealed that 19S utilizes a non-competitive mechanism of action, which was supported by fluorescence studies showing a classic sigmoidal binding profile. Studies with selected mutants of hFXIa indicated that sulfated QAOs bind in heparin-binding site of the catalytic domain of hFXIa. Overall, the approach of fragment-based design offers considerable promise for designing heparin-binding site-directed allosteric inhibitors of hFXIa.